Assessment of the vulnerable carotid atherosclerotic plaque using contrast-enhanced ultrasonography. (June 2017) - Filis, Konstantinos; Toufektzian, Levon; Galyfos, George; Sigala, Fragiska; Kourkoveli, Panagiota; Georgopoulos, Sotirios; Vavuranakis, Manolis; Vrachatis, Dimitrios; Zografos, George
Carotid atherosclerosis represents a primary cause for cerebrovascular ischemic events and its contemporary management includes surgical revascularization for moderate to severe symptomatic stenoses. However, the role of invasive therapy seems to be questioned lately for asymptomatic cases. Numerous reports have suggested that the presence of neovessels within the atherosclerotic plaque remains a significant vulnerability factor and over the last decade imaging modalities have been used to identify intraplaque neovascularization in an attempt to risk-stratify patients and offer management guidance. Contrast-enhanced ultrasonography of the carotid artery is a relatively novel diagnostic tool that exploits resonated ultrasound waves from circulating microbubbles. This property permits vascular visualization by producing superior angiography-like images, and allows the identification of vasa vasorum and intraplaque microvessels. Moreover, plaque neovascularization has been associated with plaque vulnerability and ischemic symptoms lately as well. At the same time, attempts have been made to quantify contrast-enhanced ultrasonography signal using sophisticated software packages and algorithms, and to correlate it with intraplaque microvascular density. The aim of this review was to collect all recent data on the characteristics, performance, and prognostic role of contrast-enhanced ultrasonography regarding carotid stenosis management, and to produce useful conclusions for clinical practice.